CONNELL, Raewyn. Gênero em termos reais. 1. ed. São Paulo: Nversos, 2016. - Magalhães de Figueiredo, Marcos Paulo; Lins de Almeida Filho, Carlito (Conexão Política, 2024)
CONNELL, Raewyn. Gênero em termos reais. 1. ed. São Paulo: Nversos, 2016.